2019
DOI: 10.1002/er.4631
|View full text |Cite
|
Sign up to set email alerts
|

Porous MOF‐205 with multiple modifications for efficiently storing hydrogen and methane as well as separating carbon dioxide from hydrogen and methane

Abstract: Summary In this work, quantum mechanical calculations and grand canonical Monte Carlo simulations were performed to study H2 and CH4 uptakes as well as CO2 separation from CH4 or H2 in MOF‐205 with different modification approaches. Upon C48B12 impregnation and Li decoration, B‐doped MOF‐205 shows remarkably improved gas adsorption and separation performances. Under ambient condition, both H2 and CH4 storage capacities in the modified materials meet the targets set by the US Department of Energy. Moreover, Li … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Han et al 7 adopted a new La 0.7 Sr 0.3 FeO 3−δ /(La 0.5 Sr 0.5 ) 2 CoO 4+δ composite hollow fiber membrane to separate oxygen. Xu et al 8 used porous metal organic framework (MOF)-205 to separate carbon dioxide from hydrogen and methane. Maarefian et al 9 used a hollow fiber membrane separator to separate hydrogen from ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al 7 adopted a new La 0.7 Sr 0.3 FeO 3−δ /(La 0.5 Sr 0.5 ) 2 CoO 4+δ composite hollow fiber membrane to separate oxygen. Xu et al 8 used porous metal organic framework (MOF)-205 to separate carbon dioxide from hydrogen and methane. Maarefian et al 9 used a hollow fiber membrane separator to separate hydrogen from ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…116,122 Significant researched have been conducted to investigate the hydrogen storage of MOFs at cryogenic and ambient temperature. [124][125][126][127][128][129][130][131] Latroche et al, 132 133 Other researchers have also reported the reduction in hydrogen storage capacity at elevated or ambient temperature. This problem has been attributed to the presence of weak adsorption sites on the MOFs and hydrogen.…”
Section: Mechanism Of Hydrogen Adsorption Of Mofsmentioning
confidence: 98%
“…Among tens of thousands of MOFs, ZIF‐8 is one of the most classical MOF. ZIF‐8 can be synthesized in large quantities at room temperature by using zinc nitrate and 2‐methylimidazole as raw materials at room temperature, which is easy to prepare and has high chemical stability, and has been widely studied in many fields 39,43‐47 …”
Section: Introductionmentioning
confidence: 99%